Glacier and moraine changes, glacio-hydrological dynamics and glacier-permafrost interactions at Nautgardsbrean, northeastern Jotunheimen - Thorp, Mathias Holtedahl (The University of Bergen, 2022)
Two small high-elevated polythermal glaciers and ice-cored moraine complexes situated in a zone of continuous permafrost are studied with remote sensing and field-based techniques to assess glacier changes, glacio-hydrological dynamics and interactions between the glacial, transitional and periglacial domains. A 67-year series of geodetic mass balances, elevation, volumetric, area and length changes is analyzed, revealing a particular sensitive response to climate amelioration, conforming with regional glaciers. Moraine deformation and water-parameter analysis demonstrate an interlinkage between the glacial, transitional and periglacial domains, and water as an advecting agent of heat and accelerator of landform degradation. A stepwise formation of a moraine-dammed lake seems to have enhanced ice-marginal ablation and acted as a meltwater reservoir and energy storage. Permafrost aggradation have played an important role in preserving proglacial geomorphology and retrogressively-formed longitudinal, ice-cored ridges. However, an acceleration in transformational activities such as slumping, backwasting and downwasting during the last two decades indicate geomorphological adjustment to the ongoing atmospheric warming. Glaciers of eastern Jotunheimen are particularly vulnerable to climate change due to their strong correspondence with ablation season temperatures. Additionally, small glaciers are especially prone to rapid change due to progressively lower surface albedo and conductive heat transfer from surrounding terrain. Prolonged glacier ablation and ice-core degradation will presumably promote changes in both proglacial and downstream hydrology. This study demonstrates the potential of combining remote sensing methods and in-situ observations to decode a glacial to periglacial transitional landscape. Masteroppgave i geografi GEO350 MASV-PHYG MASV-MEHA MASV-GEOG MPGEOGR